Āyakhuṃ : Śrī Jaśavanta Mahetānāṃ jīvana ane sarjana viśe - Dave, Avanti; Dalāla, Jayanti Ema., 1935-; Mahetā, Jaśavanta, 1931- (Aksharā ; prāptisthāna Pravīṇa Pustaka Bhaṇḍāra, 1983)
Festschrift honoring Jaśavanta Mahetā, b. 1931, Gujarati litterateur; comprises articles on his life and works.